Whole genome amplification - Hughes, S ed (Scion, 2005)
Whole genome amplification generates microgram quantities of genomic DNA starting from a sample of as little as a few femtograms and so is a vital technique when sample material is limited, as well as for high-throughput assays. Whole Genome Amplification: Methods Express is a comprehensive up-to-date laboratory manual for this key technique. It provides detailed step-by-step protocols as well as hints and tips for success and troubleshooting, taking readers through all aspects of whole genome amplification. This book is an essential practical guide for any researcher currently using PCR for genomic amplification or who wishes to do so in future.